Interface between Water-Solvent Mixtures and a Hydrophobic Surface - Prihoda, Annemarie; Will, Johannes; Duchstein, Patrick; Becit, Bahanur; Lossin, Felix; Schindler, Torben; Berlinghof, Marvin; Steinrück, Hans Georg; Bertram, Florian; Zahn, Dirk; Unruh, Tobias (Langmuir, 2020)
The mechanism behind the stability of organic nanoparticles prepared by liquid antisolvent (LAS) precipitation without a specific stabilizing agent is poorly understood. In this work, we propose that the organic solvent used in the LAS process rapidly forms a molecular stabilizing layer at the interface of the nanoparticles with the aqueous dispersion medium. To confirm this hypothesis, n-octadecyltrichlorosilane (OTS)-functionalized silicon wafers in contact with water-solvent mixtures were used as a flat model system mimicking the solid-liquid interface of the organic nanoparticles. We studied the equilibrium structure of the interface by X-ray reflectometry (XRR) for water-solvent mixtures (methanol, ethanol, 1-propanol, 2-propanol, acetone, and tetrahydrofuran). The formation of an organic solvent-rich layer at the solid-liquid interface was observed. The layer thickness increases with the organic solvent concentration and correlates with the polar and hydrogen bond fraction of Hansen solubility parameters. We developed a self-consistent adsorption model via complementing adsorption isotherms obtained from XRR data with molecular dynamics simulations.
CRIS-Team Scopus Importer:2020-10-30

Molecular Characterization of Mesoporous Silica (Un)loading by Gemcitabine and Ibuprofen – An Interplay of Salt-Bridges and Hydrogen Bonds - Aziz, Awin; Macht, Moritz; Becit, Bahanur; Zahn, Dirk (Journal of Pharmaceutical Sciences, 2024)
The molecular mechanisms of mesoporous silica nanomaterial (MSN) loading by gemcitabine and ibuprofen molecules, respectively, are elucidated as functions of pore geometry. Based on a small series of MSN archetypes, we use molecular dynamics simulations to systematically explore molecule-by-molecule loading of the carrier material. Apart from predicting the maximum active pharmaceutical ingredient (API) loading capacity, more detailed statistical analysis of the incorporation energy reveals dedicated profiles stemming from the interplay of guest-MSN salt-bridges/hydrogen bonding in concave and convex domains of the silica surfaces - which outcompete interactions among the drug molecules. Only after full coverage of the silica surface, we find secondary layer growth stabilized by guest-guest interactions exclusively. Based on molecular models, we thus outline a two-step type profile for drug release from MSN networks. Subject to the MSN structure, we find 50–75 % of the API within amorphous domains in the inner regions of the pores – from which drug release is provided at constant dissociation energy. In turn, the remaining 50–25 % of drug molecules are drastically hindered from dissociation.
CRIS-Team Scopus Importer:2024-02-16
Keywords: Drug release; Mesoporous silica; Solubility

Molecular Dynamics Simulations of Nitrate/MgO Interfaces andUnderstanding Metastability of Thermochemical Materials br - Shkatulov, Alexandr; Becit, Bahanur; Zahn, Dirk (ACS Omega, 2022)
We explore the role of molten nitrate interfaces onMgO surface treatment for improving the reversibility ofthermochemical energy storage via sorption and desorption ofwater or CO2. Our molecular dynamics simulations focus on meltsof LiNO3,NaNO3,KNO3, and the triple eutectic mixtureLi0.38Na0.18K0.44NO3on the surface of MgO to provide atomicscale details of adsorbed layers and to rationalize interface energies.On this basis, a thermodynamic model is elaborated to characterizethe effect of nitrate melts on the dehydration of Mg(OH)2and toquantitatively explain the difference in dehydration temperatures ofintact and LiNO3-doped Mg(OH)2.
CRIS-Team WoS Importer:2022-06-24

Molecular mechanisms of mesoporous silica formation from colloid solution: Ripening-reactions arrest hollow network structures - Becit, Bahanur; Duchstein, Patrick; Zahn, Dirk (PLoS ONE, 2019)
The agglomeration of silica nanoparticles in aqueous solution is investigated from molecular simulations. Mimicking destabilization of colloidal solutions by full removal of protective moieties or surface charge, association of SiO2/Si(OH)(4) core/shell particles leads to rapid proton transfer reactions that account for local silanole -> silica ripening reactions. Yet, such virtually barrier-less binding is only observed within a limited contact zone. Agglomeration hence leads to the formation of oligomers of nanoparticles, whilst full merging into a compact precipitate is hampered by the need for extended structural reorganisation. Implementing sufficiently fast supply from colloidal solution, our simulations show the development of silica networks comprised of covalently bound, yet not fully merged nanoparticles. Within the oligomerized nanoparticle network, coordination numbers range from 2 to 5-which is far below closest packing. Our simulations hence rationalize the formation of covalently bound network structures hosting extended pores. The resulting interfaces to the solvent show water immobilization only for the immediate contact layers, whilst the inner pores exhibit solvent mobility akin to bulk water.
CRIS-Team WoS Importer:2019-03-26

On the Role of Silica Carrier Curvature for the Unloading of Small Drug Molecules: A Molecular Dynamics Simulation Study - Macht, Moritz; Becit, Bahanur; Zahn, Dirk (Journal of Pharmaceutical Sciences, 2020)
We present atomic scale models of differently shaped silica surfaces loaded by gemcitabine and ibuprofene molecules. Despite the dissimilar nature of the drug molecules, their association to silica carriers shows quite similar characteristics. We identify a well-defined contact layer that is stabilized by silica-molecule salt-bridges/hydrogen bonding in parallel to interactions among the drug molecules. Additional loading of the carriers leads to rough films with dynamically evolving asperities rather than layer-by-layer ordering. To elucidate the role of differently shaped silica surfaces, we compared planar slab models and spherical nanoparticles as 2 limiting cases. Despite the strong difference in the curvature of the silica surfaces, our molecular dynamics simulations show only small changes of the unloading characteristics. This suggests that the design of different pore shapes in mesoporous silica–based drug carriers mainly affects the migration kinetics rather than the energetics of drug loading and release.
CRIS-Team Scopus Importer:2020-04-14
Keywords: drug delivery system(s); drug transport; molecular dynamics; molecular modeling; nanoparticle(s)

Tailoring mesoporous silica nanomaterials from molecular simulation: Modelling the interplay of condensation reactions, surfactants and space-fillers during self assembly - Becit, Bahanur; Zahn, Dirk (Microporous and Mesoporous Materials, 2021)
We outline a coarse-grained model of silica nanoparticles, hexadecetyltrimethylammonium bromide surfactants and triamethylbenzene spacers for the analysis of mesoporous silica nanomaterials (MSN) formation from molecular simulation. Starting from random configurations, molecular dynamics simulations of annealing an artificial melt allow the unprejudiced investigation of silica-surfactant/spacer self-assembly. In analogy to the experimental syntheses protocol, the second step consists of removing the spacer and surfactant species from the system, followed by condensation reactions between the silica precursors. In our coarse-grained model, this intergrowth of the silica network is described by effective potentials that mimic atomistic simulations based on quantum/classical approaches. On this basis, rapid screening of pore structures as functions of surfactant and spacer concentration is demonstrated. After characterization of the self-organization process, we finally backmap the coarsened models into atomic structures, now enabling the detailed analyses of MSN loading by guest molecules - as illustrated for gemcitabine and ibuprofen, respectively.
CRIS-Team WoS Importer:2021-06-04